Anatomical characterization of the growth of storage roots of Peruvian sweet potatoes (Ipomoea batatas (L.) Lam., Convolvulaceae) - Marín, M. (2000)
The anatomical characterization of the development of the storage root was carried out in three of sweet potato genotypes. In the initial stages differences were found in the development of the primary xylem, including the formation of a medullary parenchyma. The secondary cambial activity contributed to a great extent to the development of the storage parenchyma, determined a differential arrangement of the vascular bundles. Also simple and compound starch grains were found and the dimensions of the first were associated to the bigger size of the parenchyma. One of the genotypes presented high values in the thickness of the phellern and starch grains (123,9 µm and 29,5 µm respectively). These characteristics are suggested as parameters in the selection of sweet potato genotypes.